The Effect of Real time, Social Presence and Personalization on user’s loyalty throughout different Websites categories - FLORES GUZMAN, Guisela Denisse (The Graduate School, Ajou University, 2010)
Abstract The use of Social Presence, Personalization and Real.-time as applications for Websites in e-business has been a strong topic for research, especially the two firsts. This mainly caused by the wave of social networking sites and the inclusion of user’s contribution and interaction with the Websites (Web 2.0). The focus of this study is to reveal the basis of three selected Websites categories, Retail, Portal and Financial services, the preference of consumer applying Social Presence, Personalization and Real Time and the relationship with loyalty for the Website. Having this results, conclusions can be drawn to provide an objective and empirical evidence for e-business areas. Keywords: Social Presence, Personalization, Real-time, Loyalty
학위논문(석사)--아주대학교 국제대학원--국제경영학과,2010. 4
Keywords: Loyalty; Personalization; Real Time; Social Presence